Big Data and Global Trade Law - Burri, Mira (Social Sciences, 2021)
This multidisciplinary collection provides expert analyses on the state of global trade law in the era of Big Data and AI. It explores all areas of international economic law and includes multiple country and stakeholder perspectives. This title is also available as Open Access on Cambridge Core.